Pampas grass, free town - Uriguen, Inazio (Open Schools Journal for Open Science, 2019)
How can we turn an invaded space into a free space? Our project focused on investigating the areas of Loiu (the town where our school is located) where the invasive species of Pampas Grass, Cortadería Selloana, grow. Following the initial investigation we indicated on a paper map where these species can be found. In order to do this, we learned how to use maps, scales, locate our position, and locate the species in the mountains. Later, we investigated how to eradicate them. For this purpose, we studied the previous studies carried out by the University of the Basque Country and the work carried out by the Provincial Council of Bizkaia, eradicating the species in some specific areas of the province. Finally, we presented a dossier in the town hall. Then, the consistory informed the neighbours about how they should deal with this species, and a treatment in public areas has been undertaken. The work of our students promoted a campaign that will benefit our village.